1996
DOI: 10.1029/96jd00215
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical, actinometric, and radiometric determinations of the photolysis rate coefficient of NO2 during the Mauna Loa Observatory Photochemistry Experiment 2

Abstract: Measurements of the photolysis rate coefficient of NO2 (jNO2) were made using a chemical actinometer during the fall (September 15 to October 23, 1991), winter (January 15 to February 15, 1992), spring (April 15 to May 15, 1992), and summer (July 15 to August 15, 1992) intensives during the second Mauna Loa Observatory Photochemistry Experiment (MLOPEX 2), Hawaii. The measured clear sky jNO2 values of MLOPEX 2 for all four intensives have substantially increased over the measured jNO2 values of MLOPEX 1 (May, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 51 publications
2
53
0
5
Order By: Relevance
“…These values are in good agreement with literature (Lantz et al, 1996;Shetter et al, 1999;Kylling et al, 2005). For all below-cloud data, the experimental transmission factors, r, ranged from 0.2-1.7 for SZÃ 6SO.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These values are in good agreement with literature (Lantz et al, 1996;Shetter et al, 1999;Kylling et al, 2005). For all below-cloud data, the experimental transmission factors, r, ranged from 0.2-1.7 for SZÃ 6SO.…”
Section: Discussionsupporting
confidence: 82%
“…Near solar noon, the observed optical thickness of the clouds above the measurement site decreased considerably, and the photolysis frequency was enhanced by as much as 16%. This compares well with that of Lantz et al (1996) who reported a 24% enhancement in the actinic flux over clear sky values around local noon for cloud covers of 50% and a cloud optical depth of 4.…”
Section: Measurement Ofthe Effect Ofclouds On the Measured Jhonosupporting
confidence: 79%
“…Clouds generally reduce the actinic flux reaching Earth's surface, although temporary or local enhancements can occur with broken clouds that, as is often the case, appear brighter than the blue sky sector they obscure (Lantz et al, 1996;Crawford et al, 2003). At high altitudes above the clouds, actinic fluxes are generally enhanced by the strong up-welling radiation component from cloud reflections, and within clouds both increases and decreases of actinic fluxes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, vertical aerosol pro"les derived from airborne measurements or vertically resolved models can be used to determine the potential impact of scattering and absorption on photolysis rates. Several investigations of this type have been reported for di!erent regions with varying cloud cover, surface albedo, and solar zenith angle (Demerjian et al, 1980;Ruggaber et al, 1994;Lantz et al, 1996;Castro et al, 1997;Dickerson et al, 1997;Jacobson, 1998;Liao et al, 1999). The extensive aerosol measurements made with the Pelican provide much of the data necessary for such an analysis, thereby reducing uncertainty in the role of the aerosol in atmospheric photochemistry.…”
Section: E4ect Of the Aerosol On Photolysis Ratesmentioning
confidence: 99%